The republic of nature : an environmental history of the United States - Fiege, Mark (Mark T.) (Weyerhaeuser environmental book., 2012)
In The Republic of Nature, Mark Fiege reframes the canonical account of American history based on the simple but radical premise that nothing in the nation's past can be considered apart from the natural circumstances in which it occurred.